Coping With The Guilty Feeling In Henry James' Confidence (2008): An Individual Psychological Perspective - Handayani, Tri (2012)
The major problem of this study is how the guilty feeling is reflected in the major character's personality. The aim of this study is to analyze Henry James's Confidence novel based on the structural element and the development of the personality of the major characters based on an individual psychological perspective. The study focuses on the major characters, namely Bernard Loungeville, Gordon Wright, and Angela Vivian. The method of data collecting is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the novel; while secondary data source is include books and other data that have relation with the research. Technique of the data collecting is taking note. The technique of data analysis is descriptive study. Based on the structural analysis, Henry James wants to deliver a message that sometimes people do kindness to overcome the guilty feeling. Based on structural analysis and an Individual Psychological analysis, it is clearly that Henry James describes the psychological phenomena in which the characters (Bernard Loungeville, Gordon Wright, and Angela Vivian) of this novel has different goals of life with different problems to be solved.